2014
DOI: 10.3928/21650799-20140902-04
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Factors Associated with Pregnancy Falls

Abstract: Approximately 25% to 27% of women sustain a fall during pregnancy, and falls are associated with serious injuries and can affect pregnancy outcomes. The objective of the current study was to identify intrinsic factors associated with pregnancy that may contribute to women's increased risk of falls. A literature search (Medline and Pubmed) identified articles published between January 1980 and June 2013 that measured associations between pregnancy and fall risks, using an existing fall accident investigation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 69 publications
0
13
0
2
Order By: Relevance
“…Najczęstszą pozapołożniczą przyczyną zgonów ciężarnych są urazy, które dotyczą około 5-7% kobiet w ciąży [1]. Według innych źródeł szacuje się, że nawet 25-27% ciężarnych ulegnie upadkowi w trakcie ciąży [2]. Główną przyczyną urazów są wypadki komunikacyjne, następnie upadki z wysokości, próby samobójcze i przemoc w rodzinie [3,4,5,6].…”
Section: W St ę Punclassified
See 1 more Smart Citation
“…Najczęstszą pozapołożniczą przyczyną zgonów ciężarnych są urazy, które dotyczą około 5-7% kobiet w ciąży [1]. Według innych źródeł szacuje się, że nawet 25-27% ciężarnych ulegnie upadkowi w trakcie ciąży [2]. Główną przyczyną urazów są wypadki komunikacyjne, następnie upadki z wysokości, próby samobójcze i przemoc w rodzinie [3,4,5,6].…”
Section: W St ę Punclassified
“…The most common non-obstetrical cause of deaths in pregnancy is trauma, which amounts to 5-7% [1]. According to other sources it has been estimated that even 25-27% of pregnant women will be injured while pregnant [2]. The most common cause of trauma are transport accidents, followed by falls from heights, suicide attempts and domestic violence [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adaptations in the musculoskeletal systems are important to accommodate postural changes and altered postural balance that increases the risk of falling [13]. Falls during pregnancy occur in 25% to 27% of women [14], a rate comparable to adults aged 65 or older [15]. Falls are the second most common cause of trauma and hospitalization during pregnancy, second only to motor vehicle accidents [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, two previous review articles reviewed risks associated with falls during pregnancy [14,21]. They concluded that the musculoskeletal, sensory and psychological changes that occur during pregnancy, as well as lifestyle, could be associated with falls during pregnancy [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Se estima que una de cada cuatro mujeres embarazadas tiene al menos una caída durante el mismo (1,2,3) . Esta cifra es alarmante, ya que es comparable con la incidencia de las caídas en personas mayores de 65 años (4) . A pesar de estos datos, ha sido muy poca la investigación sobre programas de prevención de caídas dirigidos a esta población.…”
Section: Introductionunclassified